Resource Tracking in Health in Nigeria : Case Study from Niger and Ekiti States - World Bank (World Bank, Washington, DC, 2018)
In Nigeria, health care is devolved to the states and primary health care (PHC) is the responsibility of the local governments, but existing budget and capacity constraints impact delivery for an effective health program. To respond to this concern, the Federal Ministry of Health (FMOH) developed a National Strategic Health Development Plan (NSHDP, 2010-2015) prioritizing strengthening of PHC services. A partnership must be formed between the various administrative levels (federal, state and local government authorities) to support an effective delivery of PHC services. The implementation of the NSHDP requires ensuring sustainable financing, efficient use of resources as well as accountability of expenditure, for a functioning and results-oriented delivery system, and especially at the PHC level.